Inclusive Leadership and Counseling in Schools: Asylum Seekers Students - Erdal YILDIRIM (Anı Publishing, 2021)
This is a multiple case study and aimed to examine school administrators' and and psychological counselors' inclusive activities for refugee students in schools. In the study, a semi-structured interview form was used to gather the data, and analyzed with the comparative situation analysis method. With the analysis of the responses given during the faceto- face interviews conducted with school administrators and psychological counselors, the data acquired related to the inclusive activities of school administrators and psychological counselors were collected under two categories: a) Inclusive views of school administrators on refugee students and b) Inclusive views of psychological counselors on refugee students. This study's findings revealed thatrefugee students have security anxiety due to war, conflict, and violent environments and face academic failures and difficulties in establishing healthy dialogues due to language problems. The participants stated that they could not establish communication with most refugee students' families and had limited information about their life outside school. Considering the results of the study; it can be recommended to create an information network at schools containing all experiences, educational experiences, familial status, and financial losses faced by refugee students before, during, and after immigration.